CMIP6 projections of ocean warming and the impact on dimethylsulfide emissions from the Great Barrier Reef, Australia - Jackson, Rebecca L.; Woodhouse, Matthew T.; Gabric, Albert J.; Cropp, Roger A. (Frontiers in Marine Science, 2022)
Coral reefs are important regional sources of biogenic sulfur to the tropical marine atmosphere, through stress-induced emissions of dimethylsulfide (DMS). Recent estimates suggest that the Great Barrier Reef (GBR), Australia emits 0.02-0.05 Tg yr-1 of DMS (equivalent to 0.010-0.026 Tg yr-1 S), with potential implications for local aerosol-cloud processes. However, the impact of ocean warming on DMS emissions from coral reefs remains uncertain, complicating efforts to improve the representation of coral reefs in DMS climatologies and climate models. We investigate the influence of predicted changes in sea surface temperature (SST), photosynthetically active radiation (PAR) and wind speed on contemporary DMS emissions from the GBR using model output from the Coupled Model Intercomparison Project Phase 6 (CMIP6). A multiple linear regression is used to calculate seawater surface DMS (DMSw) concentration in the GBR in a contemporary (2001-2020) and end-of-century (2081-2100) scenario, as simulated by CMIP6 models under a SSP2-4.5 and SSP5-8.5 Shared Socioeconomic Pathway. By the end of this century, a 1.5-3.0°C rise in annual mean SST and a 1.1-1.7 mol m-2 d-1 increase in PAR could increase DMSw concentration in the GBR by 9.2-14.5%, leading to an increase in DMS flux of 9.5-14.3%. Previous model studies have suggested that the aerosol system has a low sensitivity to relatively large changes in coral reef-derived DMS. Therefore, the predicted change in contemporary DMS emissions is unlikely to influence the regional atmosphere. Further research is needed to understand the combined effects of temperature, light, pH, salinity and ecosystem structure on DMS production in coral reefs to better predict potential changes in emissions. Nevertheless, the findings provide insight into how predicted ocean warming may affect present-day DMS emissions and the source-strength of the GBR to the atmospheric sulfur budget.